Role of Plasma and Doping Elements on the Growth and Field Emission Properties of Metallic Carbon Nanotube (CNT) Tip Placed over Cylindrical Surface (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2015)
Carbon nanotubes (CNTs) are currently attractive materials for a diverse range of applications because of their extra ordinary mechanical and electrical properties. Their application has already been demonstrated in field emission displays, nanoscale electronic devices, biosensors and hydrogen storage medium. The field emission properties of carbon nanotubes are an important field of study because they give very high values of current density as compared to the already existing field emission devices. The effect of various factors such as plasma parameters, substitutional atoms, dimensional effects, anode-cathode distance etc. on field emission from CNT has also been extensively studied. The present talk will cover the plasma production and effect of doping of hetero-atoms on the growth and field emission properties of Carbon Nanotubes (CNTs) tip placed over a cylindrical surface in complex plasma. A theoretical model incorporating kinetics of plasma species such as electron, ions and neutral atoms including doping elements like nitrogen (N), Boron (B), Potassium (K), Cesium (Cs) and energy balance of CNTs in complex plasma has been developed. The effect of doping elements of N, B, K, and Cs on the growth of CNTs namely the tip radius has been carried out for typical glow discharge plasma parameters. It is found that doping elements affect the radius of CNTs extensively. We obtained small radii for CNT doped with N and large radius for CNT doped with B. The field emission characteristics from CNTs have therefore been suggested on the basis of results obtained. Some of theoretical results are in compliance with the existing experimental observations.
Keywords: Carbon nanotubes; Doping; Field emission; Plasma